2004
DOI: 10.1002/jgm.470
|View full text |Cite
|
Sign up to set email alerts
|

In situ single cell observation by fluorescence resonance energy transfer reveals fast intra‐cytoplasmic delivery and easy release of plasmid DNA complexed with linear polyethylenimine

Abstract: Fast endosomal escape and subsequent smooth disintegration of LPEI/pDNA in the cytoplasm are likely to be determining factors for the excellent transfection efficiency of this polyplex system. These properties may be particularly beneficial to achieve appreciably high gene expression in a prompt manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
160
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(169 citation statements)
references
References 26 publications
7
160
0
2
Order By: Relevance
“…On the contrary, Bieber et al [106] found no evidence of nuclear PEI polyplexes and mainly observed colocalization with lysosomes. Also, Itaka et al [107] observed fast release of pDNA from (linear) PEI polyplexes in the cytoplasm, questioning the long-term existence of cytoplasmic PEI polyplexes and their subsequent delivery to the nucleus. The nuclear observed PEI polyplexes in the aforementioned studies could then result from a recomplexation of pDNA and PEI polymers, after both of them reached the nuclear interior independently.…”
Section: Mitotic Partitioning Of Inorganic Quantum Dots Gold and Iromentioning
confidence: 99%
“…On the contrary, Bieber et al [106] found no evidence of nuclear PEI polyplexes and mainly observed colocalization with lysosomes. Also, Itaka et al [107] observed fast release of pDNA from (linear) PEI polyplexes in the cytoplasm, questioning the long-term existence of cytoplasmic PEI polyplexes and their subsequent delivery to the nucleus. The nuclear observed PEI polyplexes in the aforementioned studies could then result from a recomplexation of pDNA and PEI polymers, after both of them reached the nuclear interior independently.…”
Section: Mitotic Partitioning Of Inorganic Quantum Dots Gold and Iromentioning
confidence: 99%
“…Several advantages of PEI in the process of gene transfection have been reported; condensing pDNA by electrostatic interaction, binding to the cell surface and taken up by the endocytotic pathway, and releasing pDNA into the cytoplasm, via the so-called 'proton sponge mechanism' (Boussif et al, 1995;Kichler et al, 2001;Itaka et al, 2004). It was also able to accelerate gene entry into the nucleus from the cytoplasm (Pollard et al, 1998 Eagle's medium (DMEM), antibiotics (penicillin 100 U/mL; streptomycin 100 μg/mL) and other culture reagents were obtained from Invitrogen Corp. (Carlsbad, CA, USA).…”
Section: Introductionmentioning
confidence: 99%
“…8,64 Similarly, observations that co-localization of labeled complexes and the early endosomal marker Transferrin Red decreases over time suggests complexes escape from these vesicles. 15,73 In the same manner that size and charge affect both internalization and trafficking, vector composition also influences endosomal escape. Studies show that different vectors internalized and trafficked via the same mechanisms demonstrate differing escape abilities, ultimately affecting transfection.…”
Section: Endosomal Escape: Escape To the Cytosolmentioning
confidence: 99%
“…Studies show that different vectors internalized and trafficked via the same mechanisms demonstrate differing escape abilities, ultimately affecting transfection. 15,23,64 For example, polyplexes prepared with linear-or branched-PEI efficiently escape endosomes in 293T cells, whereas PLL polyplexes remained entrapped, likely due to the inability of PLL to mediate a proton-sponge effect. 15 Cellular phenotype has also been shown to influence complex escape to the cytoplasm.…”
Section: Endosomal Escape: Escape To the Cytosolmentioning
confidence: 99%
See 1 more Smart Citation